2015
DOI: 10.1111/jnc.13171
|View full text |Cite
|
Sign up to set email alerts
|

Hippocampal chromatin‐modifying enzymes are pivotal for scopolamine‐induced synaptic plasticity gene expression changes and memory impairment

Abstract: The amnesic potential of scopolamine is well manifested through synaptic plasticity gene expression changes and behavioral paradigms of memory impairment. However, the underlying mechanism remains obscure and consequently ideal therapeutic target is lacking. In this context, chromatinmodifying enzymes, which regulate memory gene expression changes, deserve major attention. Therefore, we analyzed the expression of chromatin-modifying enzymes and recovery potential of enzyme modulators in scopolamine-induced amn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
48
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(48 citation statements)
references
References 49 publications
0
48
0
Order By: Relevance
“…In addition, in a model of iron-induced memory impairment, levels of H3K9 acetylation were significantly reduced in the hippocampus of rats with neonatal iron overload, but there were no changes in the acetylation levels of H3K14ac, H4K5ac, and H4K12ac [37]. A recent study has also shown that suppressed gene expression and impaired memory are related to the downregulation of histone acetylation of H3K9 and H3K14 [38]. H3K9 is likely to be a target of HDAC1 or 3, which play crucial roles as negative regulators of long-term memory [39].…”
Section: Discussionmentioning
confidence: 90%
“…In addition, in a model of iron-induced memory impairment, levels of H3K9 acetylation were significantly reduced in the hippocampus of rats with neonatal iron overload, but there were no changes in the acetylation levels of H3K14ac, H4K5ac, and H4K12ac [37]. A recent study has also shown that suppressed gene expression and impaired memory are related to the downregulation of histone acetylation of H3K9 and H3K14 [38]. H3K9 is likely to be a target of HDAC1 or 3, which play crucial roles as negative regulators of long-term memory [39].…”
Section: Discussionmentioning
confidence: 90%
“…impairments, which typically use 100 μg/kg to 3 mg/kg doses of scopolamine (31)(32)(33). Second, the antidepressant-like effects were observed 24 hours after the final 25 μg/kg dose of scopolamine, at a time when the drug had largely been cleared.…”
Section: Figure 6 M1-achr Mediates Cholinergic Stimulation Of Sst Inmentioning
confidence: 99%
“…Furthermore, we found that increase in DNA methylation and decrease in histone acetylation at neuronal immediate early genes (IEGs) promoter was correlated with decrease in their expression and consolidation of memory during amnesia (Singh et al . ; Srivas and Thakur ). As HDAC2 does not bind directly to methylated cytosines, we explored the SIN3A‐HDAC2 co‐repressor complex‐mediated regulation of memory consolidation during amnesia.…”
mentioning
confidence: 99%